Pakistan and the Emergence of Islamic Militancy in Afghanistan - Rizwan Hussain (England Ashgate Publishing Limited, 2010)
"This study explores how the Pakistan Army's involvement with the Afghan Islamists became integrated with the Pakistani elites' post-Cold War strategic agenda. The analyses take into account the nature of the Pakistani polity and the foremost role of the Pakistani military in policy formulation." "Continued interest in the region since the events of 9/11 make this volume highly suitable for courses on South Asian studies, international relations and political Islam. It will also attract readers interested in terrorism and contemporary politics of South and West Asia."--Jacket.
Include Maps, Appendix and Bibliography
Keywords: Politics and Government -- Islamic Fundamentalism -- Diplomatic Relations